Adenylate cyclase toxin of Bordetella pertussis inhibits TLR-induced IRF-1 and IRF-8 activation and IL-12 production and enhances IL-10 through MAPK activation in dendritic cells. - Hickey, Fionnuala B; Brereton, Corinna F; Mills, Kingston H (My University, 2008)
Adenylate cyclase toxin (CyaA) of Bordetella pertussis binds to CD11b/CD18 on macrophages and dendritic cells (DC) and confers virulence to the bacteria by subverting innate immune responses of the host. We have previously demonstrated that CyaA promotes the induction of IL-10-secreting regulatory T cells in vivo by modulating DC activation. Here, we examine the mechanism of immune subversion, specifically, the modulation of TLR signaling pathways in DC. We found that CyaA synergized with LPS to induce IL-10 mRNA and protein expression in DC but significantly inhibited IL-12p70 production. CyaA enhanced LPS-induced phosphorylation of p38 MAPK and ERK in DC, and inhibitors of p38 MAPK, MEK, or NF-kappaB suppressed IL-10 production in response to LPS and CyaA. However, inhibition of p38 MAPK, MEK, and NF-kappaB did not reverse the inhibitory effect of CyaA on TLR agonist-induced IL-12 production. Furthermore, CyaA suppression of IL-12 was independent of IL-10. In contrast, CyaA suppressed LPS- and IFN-gamma-induced IFN-regulatory factor-1 (IRF-1) and IRF-8 expression in DC. The modulatory effects of CyaA were dependent on adenylate cyclase activity and induction of intracellular cAMP, as an enzyme-inactive mutant of CyaA failed to modulate TLR-induced signaling in DC, whereas the effects of the wild-type toxin were mimicked by stimulation of the DC with PGE2. Our findings demonstrate that CyaA modulates TLR agonist-induced IL-10 and IL-12p70 production in DC by, respectively, enhancing MAPK phosphorylation and inhibiting IRF-1 and IRF-8 expression and that this is mediated by elevation of intercellular cAMP concentrations.
PUBLISHED
Keywords: bacterial immunity